A phase II study of concurrent chemoradiotherapy and erlotinib for inoperable esophageal squamous cell carcinoma - Zhao, Chuanhua (Oncotarget, 2016)
Cisplatin-based concurrent chemoradiotherapy for patients with unresectable, locally advanced esophageal squamous cell carcinoma (ESCC) is associated with significant toxicities that are often intolerable. Prognosis for this subgroup of patients remains poor, and new therapeutic approaches are urgently needed. We investigated the efficacy and safety of paclitaxel combined with erlotinib and concurrent radiotherapy in patients with inoperable ESCC. Erlotinib (150 mg) was administered daily for 60 days beginning at the start of radiotherapy, and paclitaxel (45 mg/m(²)) was administered weekly along with intensity modulated conformal radiotherapy (60 Gy in 30 fractions). The median follow-up time was 21 months. The associations between EGFR and VEGF expression and treatment outcome were evaluated. Among the 21 patients treated, the overall response rate (CR + PR) was 85.6%. The median LPFS, PFS and OS were: 17.5, 14.3, and 22.9 months, respectively. Treatment-related grade 3 toxicities included esophagitis (two patients) and hypoleukemia (one patient). Grade 4 pulmonary toxicity was observed in one patient. Patients expressing EGFR had longer PFS, while those expressing VEGF or with a history of smoking had worse outcomes. Weekly paclitaxel combined with erlotinib and concurrent radiotherapy shows promise as an effective, tolerated regimen for patients with inoperable ESCC.